EXERCISE TRAINING PROTECTED CARDIAC DAMAGE FROM DOXORUBICIN-INDUCED HEART FAILURE IN SPRAGUE-DAWLEY RATS. (April 2021) - Pei, Zuowei; Zhu, Huolan; Yang, Chenguang; Ren, Yirong; Meng, Xuyang; Li, Yi; Wang, Fang
Abstract : Objective: Heart failure is a complex end stage result of various cardiovascular diseases, and has a poor prognosis. Exercise training according to oxidative stress, myocardial fibrosis, inflammation pathways improve cardiac function. The aim of this study was to investigate the possible protective effects of exercise training against cardiac damage in doxorubicin (DOX)-induced heart failure in Sprague-Dawley Rats. Figure. No caption available. Design and method: This study used 45 male Sprague-Dawley (SD) rats weighing 150 ± 20 g that were randomly divided into a control group (normal saline), doxorubicin (DOX) group and DOX plus exercise (DOX + E) group. Heart failure was induced experimentally by intraperitoneal injections of the cardiotoxic agent DOX. All groups received different treatment for 8 weeks. Blood samples were obtained from the inferior vena cava and collected in serum tubes; the blood samples were stored at minus 80°C until use. Heart tissues were fixed in 10% formalin and then embedded in paraffin for histological evaluation. The heart was stored in liquid nitrogen for immunoblotting or mRNA analysis. Results: Left ventricular fractional shortening and ejection fraction were higher in DOX + E group rats than in DOX group rats on an echocardiographic examination (Figure 1 and Table 1). Significant cardiac tissue damage (haematoxylin and eosin, Masson's trichrome staining) was seen in rats of the DOX group compared to those of the DOX + E group (Figure2). Exercise inhibited DOX-induced cardiac fibrosis (transforming growth factor, smooth muscle actin, collagen I, and collagen III) and oxidative stress (Nox4, p53) in an immunoblotting analysis (Figure 3 and 4). Conclusions: These results indicate that exercise training may be a potential therapeutic target for cardiac damage caused by DOX-induced heart failure.